The Effectiveness of Group Guidance to Prevent Body Shaming in Elementary School Students - Bagas Fevernova Wibowo Fevernova Wibowo; Minsih (Jurnal Elementaria Edukasia, 2026)
Body-shaming behavior among elementary school students can negatively impact a child's self-confidence and socioemotional development. Therefore, preventive efforts through guidance and counseling services in schools are needed. This study aims to determine the effectiveness of group guidance services in preventing body-shaming behavior among fifth-grade students at SD Gondang 6 in Sragen Regency during the 2025 academic year. The quantitative research method used is a one-group pre-test and post-test design. The study population included all fifth grade students at SD Gondang 6, and the sample was selected using a purposive sampling technique. Six students who exhibited tendencies toward body shaming behavior were selected based on the results of questionnaires completed by thirteen students. The research instruments included body-shaming questionnaires, observations, and documentation. Data analysis was performed using paired sample t-tests. The results of the analysis showed the value of GIS. (two-tailed) of 0.121 (p > 0.05), indicating there is no significant difference between the pre-test and post-test results. Group tutoring services did not significantly impact the prevention of body shaming behavior among students. In conclusion, group guidance services have not been effective in preventing body shaming behavior. Further research is recommended that uses a research design with a control group so that the effectiveness of group guidance services in preventing body-shaming behavior can be compared more objectively. Keywords: group guidance, body shaming, elementary school students, verbal bullying, behavior prevention.